Lexical familiarisation of terms from five business textbooks - Abd. Manan, Amerrudin (Penerbit UTM Press, 2007)

(untitled)
The primary focus of this study is to investigate the linguistic devices used by business textbook writers in explaining unfamiliar terms to non–business beginner undergraduates. Its secondary focus is to see if the linguistic devices carry any uniquely identifiable properties which could later be used to teach students to help them in learning new terms from their introductory business textbooks. Data for the research was elicited from five introductory business textbooks for beginner non–business undergraduates. For each textbook, the first 100 familiarised terms were selected for the study. From the selection, a small corpus was obtained comprising 1073 lexical familiarisation (LF) devices used to explain the 500 unfamiliar terms. The results of the study revealed that the LF devices found appear to have their own distinctive identities which may be recognised by students. They can be classed under two different categories: the formal–conceptual category, recognised based on their forms as well as their conceptual properties and the formal–only category recognised based on their forms only. In the formal–only category, five LF types were found; they are anaphoric familiarisation, illustration, mathematical familiarisation, acronym decomposition and translation. In the formal–conceptual category, ten LF types were found: definition, description, exemplification, paraphrase, synonymy, contrast, explanation, comparison, stipulation and analogy. For both categories, some of their properties, where applicable, were identified, namely their subgroups and their signalling devices. This study may contribute to students’ independent vocabulary learning